Implementing slicing technique on JPEG file-its impact on the download time / Fakhrul Hazman Yusoff, Anita Mohd Yasin and Rozianawaty Osman (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2005)
The following study unravels the impact of slicing an image on the download time. While JPEG compression has served Internet community well by its ability to compress big image files, limited bandwidth still causes slow download. Slicing an image is one of the methods developers employ to reduce the file size. In answering the question whether slicing lead to improved download time, image samples are taken and slicing experiments are conducted. Interestingly, slicing images if done correctly can contribute to the reduction in file size. However, image slicing has its limits. Failure to observe this limit will result in bigger file size that will render image slicing to be useless when it comes to optimum download time.